Earth in torture: technique as revenge and restatement of rationalism - Davim, David Emanuel Madeira (Sociedade & Natureza, 2017)
Responding to the critical interpretation of Nietzsche on the conventional reason we bring this written reflection on the fate of the technique and its consequences for the relationship man - Earth. For Nietzsche, the technical apparatus of the modern context brings with it the foundations of a nihilistic metaphysics and apart of the effectiveness of the concrete world. Such distancing architected and left us the legacy of environmental degeneracy so many concern us today. As proposed, the Nietzschean thought invites us to rethink the meaning of the Earth, not via simplistic abandonment of technology, but a reunion with nature, a closeness that will provide us with new possibilities of existence and action.